Kajian Keberkesanan Sistem Lampu Isyarat ‘’Countdown’’ - Mohd. Yusoff, Mohd. Firdaus (Universiti Sains Malaysia, 2006)
The study is actually focused on the effectiveness of digital countdown system which has been installed at signalised intersections at to two types of roads, which are federal roads and state roads. Generally, the study based on two approaches through e technical analysis and through the opinion of drivers in Malaysia about this system. The Level of Service and other important traffic parameters were calculated. In the technical section, the software aaSIDRA 2.0 has been used. Based on the software, the study compared the results when the time is operated and when they are not. TRAX Mite is a device used to collect the measured data, which are the axle of the vehicles, speeds and gaps of each vehicle throughout the lanes. In addition, several opinions had been taken from the drivers to see their opinion about the effectiveness of this system. Analysis was conducted and it is important to see whether the system could perform well in the next few years or not.